2004
DOI: 10.1088/0964-1726/13/3/005
|View full text |Cite
|
Sign up to set email alerts
|

Smart actuator stiffness and switching frequency in suppression of vibration of a cutting tool

Abstract: Techniques for suppression of vibration in cutting tools can save old machines and enhance design flexibility in new manufacturing systems. Structural stiffness interaction, with the use of smart materials, in an intelligent toolpost is investigated using the finite element method. The results proved the limited use of lumped modeling in driving conclusions and developing a toolpost system for dynamic response control. A transient solution is obtained for the toolpost response in which a smart material actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…For present results, toolpost dimension and, material are given in Table 1. Previous work (Rashid, M. K. 2004) indicated the use of few PWM, cycles per force period produced unfavorable switching dynamic excitation. Twenty PWM cycles for each force period produce good results more than forty has a little effect.…”
Section: Results For the Tool Time Transient Responsementioning
confidence: 99%
See 1 more Smart Citation
“…For present results, toolpost dimension and, material are given in Table 1. Previous work (Rashid, M. K. 2004) indicated the use of few PWM, cycles per force period produced unfavorable switching dynamic excitation. Twenty PWM cycles for each force period produce good results more than forty has a little effect.…”
Section: Results For the Tool Time Transient Responsementioning
confidence: 99%
“…Nature and type of signals that control smart material actuator and how can affect toolpost dynamic response suffer from scarcity of information. Recently a systematic engineering approach is used to investigate an optimum fixture-workpiece contacts property (Satyanarayana & Melkote, 2004), machining fixtures dimension (Hurtado & Melkote, 2001) and structural stiffness in toolpost dynamic (Rashid, 2004) by using the finite element approach.…”
mentioning
confidence: 99%
“…The improvement in surface quality was confirmed in these studies. Several simulation studies or experiments on machine-representative structures also demonstrated the feasibility of piezoelectric materials in vibration or chatter suppression in various turning or milling operations [62][63][64][65][66][67].…”
Section: Active and Passive Vibration Controlmentioning
confidence: 99%
“…There is scarcity of information about the nature and type of signals that control the smart material actuator and how they can affect toolpost dynamic response. Recently, a systematic engineering approach was used to investigate an optimum fixture-workpiece contact property [8], machining fixture dimension [9] and structural stiffness in toolpost dynamics [10] by using the finite element approach.…”
Section: Introductionmentioning
confidence: 99%